Rapid construction of infectious clones for distinct Newcastle disease virus genotypes - Yu, Zuhua; Zhang, Yuhao; Li, Zedian; Yu, Qingzhong; Jia, Yanyan; Yu, Chuan; Chen, Jian; Chen, Songbiao; He, Lei (Frontiers in Veterinary Science, 2023)
The reverse genetics system of Newcastle disease virus (NDV) has provided investigators with a powerful approach to understand the viral molecular biology and vaccine development. It has been impressively improved with modified strategies since its first report, but it still poses some challenges. Most noteworthy, the genome complexity and length made full-length error-free cDNA assembly the most challenging and time-consuming step of NDV rescue. In the present study, we report a rapid full-length NDV genome construction with only a two-step ligation-independent cloning (LIC) strategy, which could be applied to distinct genotypes. In this approach, the genome of NDV was divided into two segments and the cDNA clones were generated by RT-PCR followed by LIC. Subsequently, the infectious NDVs were rescued by co-transfection of the full-length cDNA clones and supporting plasmids expressing the NP, P and L proteins of NDV in BHK-21 cells. Compared to the conventional cloning approaches, the 2-step cloning method drastically reduced the number of cloning steps and saved researchers a substantial amount of time for constructing NDV infectious clones, thus enabling a rapid rescue of different genotypes of NDVs in a matter of weeks. Therefore, this two-step LIC cloning strategy may have an application to the rapid development of NDV-vectored vaccines against emerging animal diseases and the generation of different genotypes of recombinant NDVs for cancer therapy.